Analisis kondisi padang lamun di Gili Balu, Sumbawa Barat - Caterina, Natasya; Pratiwi, Made Ayu; Wijayanti, Ni Putu Putri (Jurnal Biologi Udayana; Vol 28 No 1 (2024): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2024.v28.i01.p08, 2024)
This research is conducted in seagrass meadow communities on Belang Island, Paserang Island, Kenawa Island, and Namo Island which are located in Gili Balu, West Sumbawa. Exploratory data collection was carried out in January 2022 and data processing was carried out from October to December 2022. The data collection procedure used was a training procedure for seagrass conditions using the line transect and square transect methods referring to the LIPI Seagrass Meadow Monitoring Guidebook. Data collection was carried out at each station by spreading the transect line 100 m long and placing the square transect to the right side of the line transect. Monitoring is carried out every 10 m and is carried out up to a point of 100 m. Data collection was repeated 3 times. Data processing was carried out to obtain categories and conditions of seagrass meadow compared to seagrass cover categories by the LIPI Seagrass Monitoring Guidebook and parameters of seagrass conditions by Decree of the Minister of Environment No. 200 of 2004. From the research conducted, it is found that there are 2 stations in the rare category, which are Namo and Kenawa Island, 4 stations with medium category closure of seagrass meadow, which are Paserang Island, Northwestern Belang Island, Southern Belang Island and Eastern Belang Island. The good closing category is obtained by the West Belang Island station. Seagrass meadow communities that are classified as damaged and poor are Namo Island, Kenawa Island, and Northwest Belang Island. Paserang Island and the southern and eastern parts of Belang Island are classified as damaged and unhealthy seagrass meadow. The western part of Belang Island is classified as in good and healthy seagrass condition status.